Effects of diet behaviour and sport participation on body image and body shame - Sigrún Sesselja Morthens 1991- (2016)
The study was conducted in April 2016. Participants were 92 in total, 30 males and 62 females from Reykjavik University and the age range of participants was between 20 and 38. The purpose of this study was to identify the aspects of diet behaviour and sport participation and its effects on body shame and body image. Previous studies in this area were examined to identify these factors. The hypothesis that researcher presented were that participants that have tried to lose weight are more likely to have higher body shame than those who have not tried to lose weight and females are more likely to have tried to lose weight. Also that participants with high physical activity are more likely to have a better body image and males have better body image. The results of the study showed that there was not a significant difference in in the mean levels of body shame nor body image between genders. Results also showed that sports participation and physical activity had an effect on participants’ body image but this effect was not different for males than it was for females. Keywords: body shame, body image, diet behaviour, sport participation, physical activity Rannsóknin var gerð í apríl 2016. Þátttakendur voru 92 talsins, 30 karlar og 62 konur frá Háskólanum í Reykjavík og aldur þátttakenda var á bilinu 20 til 38 ára. Tilgangur rannsóknarinnar var að bera kennsl á áhrif megrunarhegðunar og þátttöku í íþróttum á líkamlega skömm og líkamsímynd. Fyrri rannsóknir voru skoðaðar til þess að bera kennsl á þessa þætti. Tilgáturnar sem rannsakandi setti fram voru að þátttakendur sem hafa reynt að léttast eru með hærri líkamslega skömm heldur en þeir sem hafa ekki reynt að léttast og að konur eru líklegri til þess að hafa reynt að léttast. Einnig að þátttakendur sem æfa mikið eru líklegri til að hafa betri líkamsímynd og að karlar hafa betri líkamsímynd. Niðurstöður rannsóknarinnar sýndu að það var ekki marktækur munur á meðaltölum líkamlegrar skammar né líkamasímyndar milli kynja. Niðurstöður sýndu einnig að þátttaka í ...